Strategi Komunikasi Pemasaran SMA Harapan 3 Medan dalam Mendapatkan Siswa Baru di Masa Pandemi Covid-19 - Hartono, Anisya Hafila; Humaizi, Humaizi; Kurniawati, Dewi (Communication & Social Media, 2023)
This article aims to discuss the marketing communication strategy of SMA Harapan 3 Medan in getting new students during the Covid - 19 pandemic. Education is not as difficult as now because there are no obstacles to direct learning and there are no difficulties in attracting the attention of prospective new students. This happened before the era of the Covid 19 epidemic. On the other hand, this didn't really affect Harapan 3 Medan High School because they kept doing what they were doing and acted as if nothing had changed. During the Covid 19 outbreak, there were a few setbacks, but they were easy to manage and didn't present much of a challenge. We now welcome new students. In the midst of the Covid 19 outbreak, this study aims to evaluate how successful the marketing communication approach of SMA Negeri 3 Medan Harapan is in attracting new students. AIDA theory is used by many scientific communities (Attention, Interest, Desire, Action). This study uses qualitative research and data analysis techniques purposive sampling. Purposive sampling is a sampling approach in which a sample is collected from a community based on certain criteria, and this research uses this methodology. Based on the research conclusions, the marketing communication strategy developed by Harapan 3 Medan High School to recruit new students during the pandemic should welcome new students online by utilizing existing social media.